PENGARUH JUMLAH PENDUDUK, PENDAPATAN ASLI DAERAH, DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT PERTUMBUHAN EKONOMI DI PROVINSI LAMPUNG - Wibhangga Putra, Excellensio; Asmara, Kiki (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Local residents may experience happiness and wealth as a result of increased economic growth. more investigation to identify variables that may impact economic expansion. Population, local original income, and the human development index are the aspects that are brought up to illustrate how they relate to the rate of economic growth in Lampung Province between 2011 and 2022. Quantitative research methodology is employed. Secondary data for the years 2011–2022 was obtained from the Lampung Province Central Statistics Agency. SPSS version 23 is used for analysis in this study. The study's findings demonstrate that while original regional income has a positive and significant influence on the level of economic growth, population growth has a partially negative and significant influence. Original regional income has no effect on the level of economic growth. Economic growth is simultaneously influenced by population size, local original income, and human development index.